(NwOSPOMINANIQ(B.(NsBORNIK K (B25- (NLETI@ SODNQ SMERTI(B.s (NmONOGRAFIQs - (Na(B. (Nn(B. (NsKRQBINs ((NlENINGRAD s (NmUZYKAs, 1940)
(NhOTQ MNE UVI (B70 (NLET(B, (NPAMQTX ^ASTO IZMENQET MNE(B, (NNO KOGDA Q NA^INA@ WSPOMINATX SWO@ VIZNX S MINUTY POQWLENIQ W NA[EJ SEMXE(B. (NaLEKSANDRA nIKOLAEWI^A(B, (NT(B.(NE(B. (NMOEGO DOROGO {URINYKI(B, (NKAK Q PRIWYKLA NAZYWATX EGO S DETSTWA(B, (NQSNO WOZNIKAET KAVDAQ MELO^X(B, (NKASA@]AQSQ EGO(B.s
Keywords: (NMONOGRAFIQs